FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PEMILIK USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DALAM MEMILIKI NOMOR POKOK WAJIB PAJAK (NPWP) (Survey pada Wajib Pajak Pemilik UMKM yang Terdaftar di KPP Pratama Batu) - Putri, Wike Puspasari; Pusposari, Devi (Jurnal Ilmiah Mahasiswa FEB, 2013)
This reserach aimed to determine the effect of the taxpayers understanding, benefits received by taxpayer,  trust in  tax authorities and  tax socialization toward compliance  in the micro, small and medium business owners  to have a tax number. The data of this research were taken through the distribution of questionnaires to taxpayers that are specific in micro, small and medium business owners that listed on KPP Pratama Batu. Questionnaires can be used  in this research were  73  pieces.  In  this research,  researchers used  multiple linear regression analysis to test the data research. The results showed that the significant value of the taxpayer understanding variable is 0.012, the benefits received by  the taxpayer is 0.010, trust in the tax authorities is 0.024 and tax socialization is 0.036. It shows that understanding the taxpayer, benefits received by the taxpayer,  trust in the  tax authorities  and the  tax socialization have positive effect  on  compliance  in the  micro,small and medium bsiness owners to have a tax number. Keywords:  Taxpayers Understanding,  Benefits  Received by Taxpayer,  Trust in  Tax Authorities,  Tax  Socialization, Compliance  in The  Micro, Small and Medium Business Owners to Have a Tax Number